2017
DOI: 10.2139/ssrn.3044097
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Educational Attainment: Does Grit Compensate for Low Levels of Cognitive Ability?

Abstract: This study examined the role of cognitive ability in moderating grit's predictive effect on educational outcomes. Using a large, representative sample of young adults, we estimated multivariate regression models for the probability of graduating from high school, enrolling in college, earning any college degree, and earning a college degree. For each outcome, the effect of grit (and, alternatively, consistency of interest and perseverance of effort) was allowed to differ for students in each quartile of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…The correlations with fluid intelligence in Model A corroborated some of the earlier findings on the non-significant relationship between fluid intelligence and Grit [1,28,32]. The first-order Grit facets did not show a statistically significant relationship, whereas the firstorder facets Organization and Productiveness did.…”
Section: Correlations With External Criteria and Incremental Valuesupporting
confidence: 84%
See 3 more Smart Citations
“…The correlations with fluid intelligence in Model A corroborated some of the earlier findings on the non-significant relationship between fluid intelligence and Grit [1,28,32]. The first-order Grit facets did not show a statistically significant relationship, whereas the firstorder facets Organization and Productiveness did.…”
Section: Correlations With External Criteria and Incremental Valuesupporting
confidence: 84%
“…Both the incremental criterion validity of Grit over Conscientiousness and the value of distinguishing between Grit-Perseverance and Grit-Consistency have received at best mixed support by previous research. On the one hand, numerous studies have supported the predictive validity of Grit, particularly in relation to academic outcomes [1,2,11,[28][29][30][31]. In addition, some studies have suggested Grit's incremental predictive validity over Conscientiousness for other domains such as career success, career engagement, and exercise behavior [10,[32][33][34][35].…”
Section: The (Incremental) Criterion Validity Of Grit's Facets Over Cmentioning
confidence: 99%
See 2 more Smart Citations
“…We also include the standardised results of the Grit test that measures the capability of individuals of achieving long term goals. We expect that individuals scoring high on the test are more likely to be enrolled in education and/or working (Mendolia & Walker, 2014; Light & Nencka, 2019).…”
Section: Methodsmentioning
confidence: 99%